Реконструкція основних елементів комплексу військового озброєння носіїв трипільської культури - Відейко, М.Ю. (Археологія і давня історія України, 2011)
Володіючи монополією на виробництво найсучасніших видів зброї, маючи чисельну перевагу над сусідами, трипільці в період енеоліту були на території У країни домінуючою військовою силою. Не може бути жодної мови про виключно «мирний» характер давніх хліборобів та виняткову «войовничість» так званого степового населення. Владея монополией на изготовление самых современных видов вооружения, имея численное преимущество над соседями, трипольцы в период энеолита были на территории Украины доминирующей военной силой. Не может быть и речи об исключительно «мирном» характере древних хлеборобов и исключительной воинственности так называемого степного населения. Having a monopoly on the production of advanced weapons, having numerical superiorityover its neighbors, Trypilians neolithic period in the territory of Ukraine were the dominant military force betveen 5000—3000 BC. Here we consider issues related to the development of armaments and military affairs in the cultural community representatives Tripoli-Cucuteni, detail focusing on the major components of complex military weapons that were the basis of military power Trypilians for nearly two thousand years. Details will focus on the potential reconstruction of armamentand armor protection with regard to archaeological and ethnographic materials. We can consider development of weapons, such as hammer-axes, daggers, spreading of effective copper weapons. The appearance of armor and shields led to the development of offensive weapons suitable for destruction of well protected enemy. So we can observe that, as well as inthe following century, the copper age was endless race of attack and defense. The study and reconstruction of armament from Copper Age now looks promising if the use of not only the data of archeology, but also arheometrychnyh studies, involving a wide range of ethnographic data, including the adequate understanding and evaluation of materialsderived from archaeological research.